Traditional Herbal Remedies Used During Pregnancy in Indonesia: A Qualitative Study Exploring Safety and Efficacy - Fifia Ardinanti; Agnes Mariska; Dedi Sucipto (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Traditional herbal remedies are widely used during pregnancy in Indonesia. However, limited information exists regarding their safety and efficacy. This study aimed to explore the types of herbal remedies used, reasons for their use, perceived benefits and risks, and information sources guiding their use among pregnant women in Indonesia. Methods: A qualitative study was conducted involving in-depth interviews with 30 pregnant women residing in three different regions of Indonesia: urban Jakarta, rural West Java, and remote Papua. Participants were recruited through purposive sampling from community health centers and traditional birth attendant networks. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results: A wide variety of herbal remedies were reported, including ginger, turmeric, tamarind, and various leaf decoctions. Reasons for use included alleviating pregnancy-related complaints (nausea, back pain, fatigue), promoting fetal health, and easing labor. Perceived benefits included natural origin, affordability, and cultural acceptance. Concerns included potential adverse effects on the fetus and lack of scientific evidence. Information sources were primarily family members, traditional healers, and community beliefs. Notable variations in practices were observed across the three regions, reflecting diverse cultural influences and access to healthcare. Conclusion: This study highlights the widespread use of traditional herbal remedies among pregnant women in Indonesia. While perceived as natural and beneficial, safety and efficacy concerns warrant attention. Healthcare providers should engage in open dialogue with pregnant women regarding their herbal use, providing evidence-based information and culturally sensitive counseling to ensure maternal and fetal well-being.